Impact of Multiple Climate Stressors on Early Life Stages of North Pacific Kelp Species - Veronica Farrugia Drakard; Jordan A. Hollarsmith; Michael S. Stekoll (Ecology and Evolution, 2025)
ABSTRACT This study examines the effects on bull kelp (Nereocystis luetkeana) and ribbon kelp (Alaria marginata) of combinations of three climate‐related stressors relevant to high‐latitude kelp forests: temperature, salinity, and sediment load. Fertile specimens of both species were collected from Juneau, Alaska. Spores produced were cultivated over 40 days in four ecologically relevant stressor treatments: control (all stressor levels normal; CTRL), increased glacial melt (normal temperature, low salinity, high sediment load; GLAC), increased runoff (high temperature, low salinity, normal sediment load; MELT) and climate change (high temperature, low salinity, high sediment load; CLIM). Gametophyte density in both species was reduced in treatments involving high sediment load. Gametophyte density in bull kelp was also reduced in the increased runoff treatment, while ribbon kelp appeared resilient. Gametophytes of A. marginata grew equally in the increased glacial melt treatment as in the control and exhibited some growth in the increased runoff treatment. Conversely, gametophytes of N. luetkeana exhibited low growth in all treatments other than the control. A large number of gametophytes of both species were unidentifiable as either male or female in high‐temperature treatments. This likely had impacts on reproduction, as neither species was able to produce eggs or sporophytes in these treatments. The results presented here show that both N. luetkeana (a subtidal canopy‐former) and A. marginata (an intertidal subcanopy species) are sensitive to combinations of thermal, hyposaline, and sediment stress. This may have an impact on the development of gametophytes and successful reproduction in these species and may therefore have implications for the ongoing persistence of wild kelp populations in future ocean conditions.